2015
DOI: 10.1017/s1574019615000346
|View full text |Cite
|
Sign up to set email alerts
|

Gauweiler and the Outright Monetary Transactions Programme: The Mandate of the European Central Bank and the Changing Nature of Economic and Monetary Union

Abstract: On 16 June 2015 the European Court of Justice delivered its decision in the Gauweiler case, 1 concerning the legality of the Outright Monetary Transactions Programme of the European Central Bank. The Court considered the Programme compatible with EU law, as long as certain safeguards are observed in its implementation. The decision has important implications for the powers of the European Central Bank, the constitutional framework of the EU's Economic and Monetary Union, and for the relationship between the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…33 Indeed, these two tools OMT and QE, expected to provide financial support to some Eurozone countries under strict conditionality, prove how blurred is the boundary between economic and monetary policy, although the Court of Justice has confirmed that they fall in the remit of monetary policy exclusively. 34 Even more crucial for the assertion on the ambiguous nature of monetary policy as an EU exclusive competence is the design of the governance of this policy, which is not administered according to the EU traditional architecture but rather by the "Eurosystem" composed of the ECB plus the to date 19 national central banks, i.e. independent actors from legislatures and executives both in the EU and in the Eurozone countries.…”
Section: Seclusion Cooperation and Competition In Economic And Monetmentioning
confidence: 99%
“…33 Indeed, these two tools OMT and QE, expected to provide financial support to some Eurozone countries under strict conditionality, prove how blurred is the boundary between economic and monetary policy, although the Court of Justice has confirmed that they fall in the remit of monetary policy exclusively. 34 Even more crucial for the assertion on the ambiguous nature of monetary policy as an EU exclusive competence is the design of the governance of this policy, which is not administered according to the EU traditional architecture but rather by the "Eurosystem" composed of the ECB plus the to date 19 national central banks, i.e. independent actors from legislatures and executives both in the EU and in the Eurozone countries.…”
Section: Seclusion Cooperation and Competition In Economic And Monetmentioning
confidence: 99%
“…This section begins with a brief review of the OMT programme and summary of the Court's principal conclusions in Gauweiler on its compatibility with the EU Treaty framework (see also Borger, ; Craig and Markakis, ; Hinarejos, ). It then highlights the significance of the decision with respect to the relationship between the Court of Justice and the German Federal Constitutional Court as constitutional actors in EU integration.…”
Section: Case C‐62/14 Gauweiler and Othersmentioning
confidence: 99%
“…Eight decades after Carl Schmitt expressed those concerns in Berlin, the thorny question of central banks' 'neutral powers' has re-emerged. Indeed, the resort by the European Central Bank (ECB) to unconventional monetary policies -especially after the Gauweiler decision of the European Court of Justice in which the Court deemed these policies to be in line with the Treaties (Hinarejos, 2015, 563 ss) -as well as the creation of the (first) supervisory pillar of the Banking Union have drawn attention to the 'enlargement' of the ECB's functions in times of crisis. The ECB is now undoubtedly a key actor in the European Union's (EU) economic governance.…”
Section: Introductionmentioning
confidence: 99%